The Impact of Taxation on Economic Growth: Case Study of OECD Countries - Rudolf Macek (Review of Economic Perspectives, 2015)
The aim of this paper is to evaluate the impact of individual types of taxes on the economic growth by utilizing regression analysis on the OECD countries for the period of 2000–2011. The impact of taxation is integrated into growth models by its impact on the individual growth variables, which are capital accumulation and investment, human capital and technology. The analysis in this paper is based on extended neoclassical growth model of Mankiw, Romer and Weil (1992), and for the verification of relation between taxation and economic growth the panel regression method is used. The taxation rate itself is not approximated only by traditional tax quota, which is characteristic by many insufficiencies, but also by the alternative World Tax Index which combines hard and soft data. It is evident from the results of both analyses that corporate taxation followed by personal income taxes and social security contribution are the most harmful for economic growth. Concurrently, in case of the value added tax approximated by tax quota, the negative impact on economic growth was not confirmed, from which it can be concluded that tax quota, in this case as the indicator of taxation, fails. When utilizing World Tax Index, a negative relation between these two variables was confirmed, however, it was the least quantifiable. The impact of property taxes was statistically insignificant. Based on the analysis results it is evident that in effort to stimulate economic growth in OECD countries, economic-politic authorities should lower the corporate taxation and personal income taxes, and the loss of income tax revenues should be compensated by the growth of indirect tax revenues.
Keywords: 330